Quantifying Tree Diversity, Carbon Stocks, and Sequestration Potential for Diverse Land Uses in Northeast India - Sahoo, Uttam Kumar; Tripathi, Om Prakash; Nath, Arun Jyoti; Deb, Sourabh; Das, Dhruba Jyoti; Gupta, Asha; Devi, N. Bijayalaxmi; Charturvedi, Shiva Shankar; Singh, Soibam Lanabir; Kumar, Amit; Tiwari, Brajesh Kumar (Frontiers in Environmental Science, 2021)
In the modern era, rapid anthropogenic activities in the vicinity of the Himalayas disturb the carbon sequestration potential resulting in climate change. For the first time, this study estimates biomass and carbon storage potential of northeast India’s under diverse land uses through a biomass estimation model developed for this region. The mean tree density in tropical, subtropical, and temperate forests was 539, 554, and 638 trees ha-1 respectively. The mean vegetation carbon stock was highest for temperate forest (122.09 Mg C ha-1) followed by sub-tropical plantations (115.45 Mg C ha-1), sub-tropical forests (106.01 Mg C ha-1), tropical forests (105.33 Mg C ha-1), tropical plantations (93.00 Mg C ha-1), and temperate plantations (50.10 Mg C ha-1). A moderate linear correlation was found between aboveground biomass carbon (AGBC) and tree species richness in tropical forest (r=0.260., P<0.05) and temperate forests (r=0.573, P<0.001). Among the forests, the mean soil organic carbon (SOC) stock up to 45 cm depth was highest for tropical forests (72.54 Mg C ha-1) followed by temperate forests (63.4 Mg C ha-1), and sub-tropical forests (42.58 Mg C ha-1). A strong relationship between tree basal area and biomass carbon storage was found for all land-use types. The land use transformation from agriculture to agroforestry, and grassland to plantations increased both vegetation carbon (VC) and SOC stocks. The corresponding increase in VC and SOC was 40.80 and 43.34 Mg C ha-1 respectively in the former, and 83.18 and 97.64 Mg C ha-1 in the latter. In general, the landscape level estimates were drawn from site-level estimates in a given land-use type, and therefore the corresponding values might be overestimated. We found a complex and highly variable relationship between AGBC and tree diversity. Due to lack of consistency in the relation between carbon stock and diversity measures; it was concluded that biodiversity conservation and its promotion may not enhance biomass carbon storage in the various land use types. The results provide baseline information on carbon stock which may serve as a reference for devising appropriate land use change policies in the region.